TANTANGAN DAN PROSPEK SYARIAH ENTREPRENEURSHIP KE DEPAN - Muhammad Ilham; Ridwan; Mukhtar Luthfi; Abdul Wahid Haddade (Makkah: Journal Of Islamic Studies, 2025)
This study aims to comprehensively analyze the challenges, opportunities, and adaptation strategies of Shariah entrepreneurship in responding to global market dynamics and the development of the Industrial Revolution 4.0. The increasing global awareness of the halal lifestyle has positioned Shariah entrepreneurship as a sector with significant growth potential. However, Shariah-based business actors continue to face fundamental challenges, including the complexity of cross-border halal certification processes, low levels of Islamic financial literacy, limited access to capital, and the suboptimal utilization of digital technology. On the other hand, technological advancements such as blockchain, big data, and Islamic fintech present substantial opportunities to create a more transparent, efficient, inclusive, and accountable business ecosystem. This study concludes that the key to the future success of Shariah entrepreneurship lies in the synergy between the implementation of Islamic ethical values grounded in Maqasid Shariah and digital technological innovation. Adaptation strategies through the digitalization of the halal supply chain, enhancement of digital literacy, and the strengthening of ethics-based universal branding are crucial steps to enable Shariah entrepreneurs to compete in international markets while contributing meaningfully to economic development and societal well-being.